PENERAPAN METODE BERMAIN FLASHCARD UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG ANAK KELOMPOK B DI RA AL AMIN PAKIS MALANG - Mar’atush Sholihah; Mohammad Afifulloh; Yorita Febry Lismanda (UNISMA, 2019)
The faced problem is the low counting ability of children, that its sense is less satisfactory. In delivering lessons of learning, the teacher writes numbers firstly without introducing symbols, also for the teacher's method is monotonous so, the children get bored quickly. To solve the problem, the researcher take action by designing of learning process activities in the classroom with the application of the flashcard playing method to improve the numeracy skills of group B children in RA Al Amin Pakis Malang. The implementation of this class research was conducted in 2 cycles, that compose 4 stages: the planning stage, the implementation stage, the observation stage and the reflection stage. The first Cycle was carried out by obtaining 50% or 8 out of 16 children, who reached the expected indicators. Therefore, the research was conducted again. In the second cycle, there was a progress at 87.5% or 12 of 16 children, who reached the expected indicators. Finally, from this classroom action research, it can be seen that the development of children's numeracy capacity has increased.